Analisa Efektivitas Penggunaan Jembatan Penyeberangan Orang di Depan Mall Kota Jayapura - Penias Lepki; Irja Tobawan Simbiak; Monita Yessy Beatrick (Jurnal Sipil Terapan, 2024)
The People Crossing Bridge (JPO) is one of the important infrastructures in the urban transportation system. JPO is designed to facilitate pedestrians to cross the highway safely without being disturbed by vehicle traffic. This infrastructure not only serves to improve safety but also supports mobility efficiency in dense urban areas. On Jalan Dr. Sam Ratulangi, Jayapura City, a pedestrian bridge infrastructure was built, which is located in front of Jayapura Mall, Jayapura City. According to its purpose, the pedestrian bridge was built to reduce the occurrence of traffic accidents in locations with heavy activities, including city centers with shopping that certainly has high mobility. The data collection method in this study uses the survey method. In this study, the researcher conducted a survey of JPO facilities at pedestrian trap sites. This research is the output of the stages that have been carried out by the author. Based on the results of observations that have been carried out on July 8 and 13, 2024, at 07.00 – 17.00 WIP, the results were found that more pedestrians chose to cross using the available JPO with a total of 147 people (65%), compared to 92 people (35%) who did not use the JPO. Meanwhile, using JPO can help and facilitate and shorten the travel time of the crossing, by climbing and descending stairs you can enjoy the atmosphere around. In the condition of the JPO floor, this is due to the presence of mischievous individuals so that public facilities are starting to be unattractive to see. For this reason, public facilities are assets that we need to take care of together so that they are suitable for use. Factors that affect the effectiveness of the JPO located on jl. Dr. Sam Ratulangi in front of the Jayapura City Mall that needs to be concerned is the cleanliness at the location is the top priority.